Enhanced high-harmonic generation up to the soft X-ray region driven by mid-infrared pulses mixed with their third harmonic - Kroh, Tobias; Jin, Cheng; Krogen, Peter; Keathley, Philip D.; Calendron, Anne-Laure; Siqueira, Jonathas P.; Liang, Houkun; Falcão-Filho, Edilson L.; Lin, C. D.; Kärtner, Franz X.; Hong, Kyung-Han (My University, 2018)
We systematically study the efficiency enhancement of high-harmonic generation (HHG) in an Ar gas cell up to the soft X-ray (SXR) range using a two-color laser field composed of 2.1 μm (ω) and 700 nm (3ω) with parallel linear polarization. Our experiment follows the recent theoretical investigations that determined two-color mid-infrared (IR) pulses, mixed with their third harmonic (ω + 3ω), to be close to optimal driving waveforms for enhancing HHG efficiency in the SXR region [Jin et al., Nature Comm. 5, 4003 (2014)]. We observed sub-optical-cycle-dependent efficiency enhancements of up to 8.2 of photon flux integrated between 20 – 70 eV, and up to 2.2 between 85 – 205 eV. Enhancement of HHG efficiency was most pronounced for the lowest tested backing pressure (≈ 140 mbar), and decreased monotonically as the pressure was increased. The single-color (ω)-driven HHG was optimal at the highest backing pressure tested in the experiment (≈ 375 mbar). Our numerical simulations based on single-atom response and 3D pulse propagation show good qualitative agreement with experimental observations. The lower enhancement at high pressure and higher photon energy indicates that phase matching of two-color-driven HHG is more sensitive to ionization rate and pulse propagation effects than the single-color case. We show that with further improvements to the relative phase jitter and the spatio-temporal overlap of the two beams, the efficiency enhancement could be further improved by at least a factor of ≈ 2.
Citation: Kroh, T., Jin, C., Krogen, P., Keathley, P. D., Calendron, A.-L., Siqueira, J. P., … Hong, K.-H. (2018). Enhanced high-harmonic generation up to the soft X-ray region driven by mid-infrared pulses mixed with their third harmonic. Optics Express, 26(13), 16955–16969. https://doi.org/10.1364/OE.26.016955
Keywords: Harmonic generation and mixing; Soft x-rays; Strong field laser physics; Ultraviolet